Race for the Future - Clement, Matt (Social justice, 2020)
The article examines the social and political developments in Great Britain, particularly the struggles between the radical left and racist right in advancing social justice. Other topics include the mass movements against the austerity measures implemented by the government in 2011, as well as the relationships between new social movements like the People's Assembly Against Austerity and the Labour Party and trade unions.